IECON 2017 - 43rd Annual Conference of the IEEE Industrial Electronics Society 2017
DOI: 10.1109/iecon.2017.8216398
|View full text |Cite
|
Sign up to set email alerts
|

A secondary-control based fault current limiter for four-wire three phase inverter-interfaced DGs

Abstract: Abstract-Fault current limiters (FCLs) are one class of solutions to cope with the upcoming challenges in microgrid protection. Considering high penetration of distributed generations (DGs) in microgrids, the necessity of designing cheap and effective FCL is getting higher. This paper attempts to fill this gap by proposing an embedded FCL operating based on modifying the secondary control of DGs. As this method is designed for fourwire system, besides cost-effectiveness, it has independency and flexibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…In this section, the four scenarios simulated in Section 4.2.3 are reproduced in the experimental platform to validate the real capabilities of the proposed fault current limitation strategy. In the following lines, it is demonstrated that the time response for the fault current limitation action and voltage recovery offers superior time responses than in the current literature [38][39][40].…”
Section: Short-circuit Proof Algorithmmentioning
confidence: 94%
See 1 more Smart Citation
“…In this section, the four scenarios simulated in Section 4.2.3 are reproduced in the experimental platform to validate the real capabilities of the proposed fault current limitation strategy. In the following lines, it is demonstrated that the time response for the fault current limitation action and voltage recovery offers superior time responses than in the current literature [38][39][40].…”
Section: Short-circuit Proof Algorithmmentioning
confidence: 94%
“…Different types of short circuits are studied in [38], but the fault current limitations offer dynamics of about 200 ms to achieve steady-state, while in [39] only a tretrapolar short-circuit is evaluated obtaining time responses of about 100 ms. In [40], some results are just simulated for AC droop-based four-wire systems. Finally, other alternatives exist applied to series filters or obtaining FCL by changing the output inductances as detailed in [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Utilising a fault current limiters (FCLs): An ideal FCL is the series device suppressing fault current of DG or branch by increasing its impedance from zero to a high value in a fast manner to enable coordination of protection [83,84]. Up to now, passive FCL (PFCL), superconducting FCL (SFCL), solid-state FCL (SSFCL), and controlled-based FCL to reach the promising goal [85]. Although FCL permits higher DG installation, the initial cost of FCL, the high recovery time of SFCL, and switching losses of SSFCL are the main drawbacks.…”
Section: γ1 Topology Changes and Ders Impactsmentioning
confidence: 99%
“…Because VI fluctuates between a zero and nonzero value when the required VI is lower than selected maximum values. The objective of this study, which is an extension of the work proposed in [7], is addressing the aforementioned problems of VI-based FCL. To this end, a secondary control-based FCL is presented to limit the fault current to twice its nominal value for a four-wire three-phase DG working in the Voltage-Control Mode (VCM).…”
Section: Introductionmentioning
confidence: 99%